Correlation of Indoleamine-2, 3-Dioxygenase and Chronic Kidney Disease: A Pilot Study. (6th January 2021) - Pan, Binbin; Zhang, Feng; Sun, Jian; Chen, Dawei; Huang, Wenjuan; Zhang, Hao; Cao, Changchun; Wan, Xin
Abstract : Objective. To explore the correlation of indoleamine-2, 3-dioxygenase (IDO) and chronic kidney disease (CKD). Methods . A total of 154 CKD patients and 42 non-CKD patients were recruited. Patients were grouped into ACR1 ACR3 (<30 mg/g, 30-300 mg/g, and >300 mg/g). Biomarkers in different groups were compared by ANOVA. Correlation was calculated by Pearson or Spearman analysis and binary logistic regression. The ROC curve was also performed. Results. The levels of albumin, serum creatinine (sCr), and IDO in non-CKD patients were significantly different from those in CKD3-CKD5 stages (p < 0.05 ). IDO was correlated with age, proteinuria, ACR, and eGFR (p < 0.01 ). After adjusting for CKD-related indices, ln(IDO) was an independent risk factor for CKD (3.48, p < 0.05 ). The analysis of ROC curve revealed a best cutoff for IDO was 0.0466 and yielded a sensitivity of 83.8% and a specificity of 75%. Hemoglobin, total protein, and albumin in the ACR1 group were significantly higher than those in the ACR2 and ACR3 groups (p < 0.01 ), while sCr and IDO levels were significantly lower than those in the ACR2 and ACR3 groups (p < 0.01 or p < 0.05 ). After adjusting for CKD-related indices, ln(IDO) was still an independent risk factor for ACR (OR = 2.7, p < 0.05 ). The analysis of ROC curve revealed a best cutoff for IDO was 0.075 and yielded a sensitivity of 71.9% and a specificity of 72.2%. Conclusion . IDO may be a promising biomarker to predict CKD and assess kidney function.